In-depth evaluation of nutritive, chemical constituents and anti-glycemic properties of jackfruit (Artocarpus heterophyllus Lam) clonal accessions with flake colour diversity from Eastern Sub-Himalayan plains of India. (1st May 2023) - Natta, Suman; Pal, Kumaresh; Kumar Alam, Bharath; Mondal, Debayan; Kumar Dutta, Sudip; Sahana, Nandita; Mandal, Somnath; Bhowmick, Nilesh; Sankar Das, Soumitra; Mondal, Prithusayak; Kumar Pandit, Goutam; Kumar Paul, Prodyut; et al.
Graphical abstract: Highlights: Fifteen clonal jackfruit accessions with flake colour variation were selected. Flakes with higher soluble sugar and TSS: acid ratio were sweeter in taste. Orange-red and deep yellow-coloured flakes were medicinally superior. Nineteen anti-diabetic compounds were detected in the flakes. Orange-red-coloured flakes exhibited better enzyme inhibition. Abstract: The study was designed to elucidate the potential of jackfruit clonal accessions having diverse flake colours from nutritional and medicinal perspectives. Jack fruit accessions with deep yellow flakes were found to contain the highest flavonoids, antioxidant activity, ascorbic acid, and α-glucosidase inhibition whereas, orange-red flakes exhibited the highest β-carotene, phenol, minerals (iron and zinc) and better inhibition of α-amylase and β-glucosidase enzymes. Phenolic compounds profiling revealed the presence of higher sinapic acid, ferulic acid and quercetin contents in the orange-red-coloured flakes. Metabolite analysis revealed presence of anti-diabetic compounds ( n -Hexadecanoic acid, tridecane, 2-Heptadecenal etc.) in deep yellow and orange-red coloured jack flakes with lower glycemic load. Considering the abundant health benefits as evident from the present study, orange-red and deep yellow-coloured flakes may be recommended for consumption to manage the hyperglycemic condition.